Modal Sosial Pedagang Konvensional di Kota Makassar - Smandra, Mario; Usman, Musrayani (Multiverse: Open Multidisciplinary Journal, 2023)
The rapid development of online commerce has led to changes in consumer actions and behavior, which has forced conventional traders to find ways to survive. This study aims to find out the extent to which social capital consisting of beliefs, networks and values or norms to see conventional merchants survive with the rise of online commerce or e-commerce. The theoretical approach used is social interaction theory and rational choice theory, The results of the study show that social capital has an important role in survival, especially social relationships, norms and beliefs. This shows that social interaction is needed as social capital and a rational choice to continue trading conventionally. Social capital becomes a significant source of social power, which provides access to opportunities, resources, information and support within society. E-commerce activities indirectly erode the existence of conventional merchants, thus requiring conventional merchants to follow technological developments to be more competent with e-commerce.